Primary Cutaneous Anaplastic Large-Cell Lymphoma With Aberrant CD20 Expression: Case Report and Review of the Literature. (1st December 2022) - Mark, Erica; Sutton, Mark; Gru, Alejandro
Abstract: Cutaneous CD20 + T-cell lymphomas are exceedingly rare. Differentiating cases of T-cell lymphoma with aberrant expression of the B-cell marker CD20 from B-cell lymphoma may be associated with misdiagnosis or delays in diagnosis. We report, to the authors' knowledge, the first case of CD20 + primary cutaneous anaplastic large-cell lymphoma and review the literature to characterize published cases of CD20 + cutaneous T-cell lymphoma (n = 40). There is no accepted explanation for this phenomenon; however, it is suspected that these cases may be due to neoplastic transformation of CD20 + T cells or that CD20 may represent a T-cell activation marker. Expression of CD20 may have clinical significance in prognostication and consideration of treatment options with anti-CD20 therapies such as rituximab.